Melanoma xenotransplant on the chicken chorioallantoic membrane: a complex biological model for the study of cancer cell behaviour - Strnadová, Karolína; Španko, Michal; Dvořánková, Barbora; Lacina, Lukáš; Kodet, Ondřej; Shbat, Andrej; Klepáček, Ivo; Smetana, Karel (Histochemistry and cell biology, 2020)
The globally increasing incidence of cancer, including melanoma, requires novel therapeutic strategies. Development of successful novel drugs is based on clear identification of the target mechanisms responsible for the disease progression. The specific cancer microenvironment represents a critically important aspect of cancer biology, which cannot be properly studied in simplistic cell culture conditions. Among other traditional options, the study of melanoma cell growth on the chicken chorioallantoic membrane offers several significant advantages. This model offers increased complexity compared to usual in silico culture models and still remains financially affordable. Using this model, we studied the growth of three established human melanoma cell lines: A2058, BLM, G361. The combination of histology, immunohistochemistry with the application of human-specific antibodies, intravascular injection of contrast material such as filtered Indian ink, Mercox solution and phosphotungstic acid, and X-ray micro-CT and live-cell monitoring was employed. Melanoma cells spread well on the chicken chorioallantoic membrane. However, invasion into the stroma of the chorioallantoic membrane and the limb primordium graft was rare. The melanoma cells also significantly influenced the architecture of the blood vessel network, resulting in the orientation of the vessels to the site of the tumour cell inoculation. The system of melanoma cell culture on the chorioallantoic membrane is suitable for the study of melanoma cell growth, particularly of rearrangement of the host vascular pattern after cancer cell implantation. The system also has promising potential for further development.
Keywords: Chick Embryo; kur domácí; Animals; biologické modely; Chickens; Chorioallantoic membrane; Chorioallantoic Membrane; Immunohistochemistry; lidé; Models, Biological; Cancer-associated fibroblasts; nádorové buňky kultivované; Melanoma invasiveness; imunohistochemie; Cancer microenvironment; Tumor Cells, Cultured; Embryo; melanom experimentální; Melanoma, Experimental; zvířata; chorioalantoická membrána; kuřecí embryo; Melanoma; Humans